HIV-1 Tat-shortened neurite outgrowth through regulation of microRNA-132 and its target gene expression. Issue 1 (December 2016) - Rahimian, Pejman; He, Johnny
Abstract Background Synaptodendritic damage is a pathological hallmark of HIV-associated neurocognitive disorders, and HIV-1 Tat protein is known to cause such injury in the central nervous system. In this study, we aimed to determine the molecular mechanisms of Tat-induced neurite shortening, specifically the roles of miR-132, an important regulator of neurite morphogenesis in this process. Methods The relationship between Tat expression and miR-132 expression was first determined using reverse transcription quantitative PCR (qRT-PCR) in Tat-transfected astrocytes and neurons, astrocytes from Tat-transgenic mice, and HIV-infected astrocytes. qRT-PCR and Western blotting were performed to determine Tat effects on expression of miR-132 target genes methyl CpG-binding protein 2, Rho GTPase activator p250GAP, and brain-derived neurotrophic factor. Exosomes were isolated from Tat-expressing astrocytes, and exosomal microRNA (miRNA) uptake into neurons was studied using miRNA labeling and flow cytometry. The lactate dehydrogenase release was used to determine the cytotoxicity, while immunostaining was used to determine neurite lengths and synapse formation. Tat basic domain deletion mutant and miR-132 mimic and inhibitor were used to determine the specificity of the relationship between Tat and miR-132 and its effects on astrocytes and neurons and the underlying mechanisms of Tat-induced miR-132 expression. Results Tat significantly induced miR-132 expression, ensuing down-regulation of miR-132 target genes in astrocytes and neurons. miR-132 induction was associated with phosphorylation of cAMP response element-binding protein and required the basic domain of Tat. miRNA-132 induction had no effects on astrocyte activation or survival but was involved in the direct neurotoxicity of Tat. miR-132 was present in astrocyte-derived exosomes and was taken up by neurons, causing neurite shortening. Conclusions Tat-induced miR-132 expression contributes to both direct and astrocyte-mediated Tat neurotoxicity and supports the important roles of miR-132 in controlling neurite outgrowth.